Linear aggregation of economic relations - Theil, Henri (Amsterdam : North-Holland Pub. Co., 1965)
This essay represents an attempt to deal with the problem of aggregation; that is, of the relationship between macroeconomics and microeconomics. In the author's view, this is to be ascribed to the fact that only a mixture of an economic and a statistical approach has a chance of being successful in this field - successful both in a theoretical and in an empirical respect.
Includes bibliographical footnotes and index.
rpm 05/09/2017
Loans
Keywords: Set theory; Statistics